2012
DOI: 10.17221/164/2011-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of fertility restoration of the A<sub>4</sub> cytoplasmic-nuclear male sterility system in pearl millet

Abstract: Abstract:Inheritance of fertility restoration of the A 4 system of cytoplasmic-nuclear male sterility in pearl millet was investigated using six crosses between two diverse male sterile lines (A-lines) and three diverse restorers (R-lines). The segregation pattern of male sterile (S) and male fertile (F) plants observed in F 2 , and BC 1 in two seasons at ICRISAT, Patancheru, indicated the dominant single-gene control of male fertility restoration. The segregation pattern in BC 1 F 2 progenies derived from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 10 publications
3
15
1
Order By: Relevance
“…Thus, overall results of this study showed that same gene is present in all the four restorer lines for A 1 and A 4 , respectively. This result is concomitant with the earlier study in pearl millet which reported single dominant gene to be responsible for inheritance of fertility restoration of A 1 and A 4 cytoplasm (Yadav et al 2010 andGupta et al 2012). Though earlier study in pearl millet reported possibilities of two or three genes responsible for restoration of A 1 cytoplasm (Yadav et al 2010), but absence of sterile plants in segregating generations of A 1 restorers involved in this study indicated the presence of same restorers gene across all four A 1 restorers.…”
Section: )supporting
confidence: 88%
See 1 more Smart Citation
“…Thus, overall results of this study showed that same gene is present in all the four restorer lines for A 1 and A 4 , respectively. This result is concomitant with the earlier study in pearl millet which reported single dominant gene to be responsible for inheritance of fertility restoration of A 1 and A 4 cytoplasm (Yadav et al 2010 andGupta et al 2012). Though earlier study in pearl millet reported possibilities of two or three genes responsible for restoration of A 1 cytoplasm (Yadav et al 2010), but absence of sterile plants in segregating generations of A 1 restorers involved in this study indicated the presence of same restorers gene across all four A 1 restorers.…”
Section: )supporting
confidence: 88%
“…Precise knowledge of genetics of fertility restoration is an essential for restorer breeding program and also important to know any intergenic interactions. Earlier studies reported single dominant gene to be responsible for the inheritance of fertility restoration of A 1 and A 4 cytoplasm though possibility of di-and tri-genic inheritance of fertility restoration was also proposed earlier for A 1 CMS system (Yadav et al 2010;Gupta et al 2012). Till date, ICRISAT had developed about 170 seed-parents, of which about 130 are based on A 1 and A 4 CMS systems, and also developed about 80 restorers since 2006 .…”
Section: Introductionmentioning
confidence: 99%
“…The A 4 male‐fertility restoration genes are most likely dominantly monogenically inherited, according to Gupta et al. () and phenotypic data from Pucher et al. ().…”
Section: Requirements For Commercial Hybrid Seed Production: the Cytomentioning
confidence: 99%
“…However, screening of OPVs for fertility restoration ability is challenging and still incomplete (Rai, Kulkarni, Thakur, Haussmann, & Mgonja, 2006). More recently published research suggests screening WA germplasm for A 4 male-fertility restoration genes or transferring them via backcrossing into WA-adapted material with pure phenotypic or better marker-assisted selection (Gupta, Rai, Govindaraj, & Rao, 2012;Pucher et al, 2018). The A 4 male-fertility restoration genes are most likely dominantly monogenically inherited, according to Gupta et al (2012) and phenotypic data from Pucher et al (2018).…”
Section: Requirements For Commercial Hybrid Seed Production: the Cytomentioning
confidence: 99%
See 1 more Smart Citation